Estudo clínico-epidemiológico da infecção por Leishmania sp em um abrigo de cães em área endêmica de leishmaniose visceral na região metropolitana de Natal, Rio Grande do Norte - Silva, Alessandra Salles da (2023)
Visceral leishmaniasis (VL) occurs as a chronic infectious anthroponzoonosis with worldwide distribution. Most cases of VL occur in Brazil, East Africa, and India with 50,000 to 90,000 new human cases annually. In 2020 more than 90% of new cases were reported in Brazil, China, Ethiopia, Eritrea, India, Kenya, Somalia, Sudan, South Sudan and Yemen. VL is considered an urban and public health problem associated with socio-environmental vulnerability. The domestic dog is the main animal reservoir of Leishmania infantum since it makes the correlation between rural and urban spaces and lives in public spaces and homes. The phebotomine Lutzomyia longipalpis is the vector of L. infantum. In order to provide basic care for abandoned animals, several countries and regions have shelters animals. In Brazil, many emerged in a disorganized way, overcrowded and with risks of contamination of infectious and contagious diseases among individuals. Therefore, the objectives of this study were to evaluate the health status of dogs in a shelter in the metropolitan region of Natal, through physical-clinical and laboratory tests and to determine the occurrence of L. infantum infection and tick born parasites as Ehrlichia canis and Babesia sp. Initially, qualitative information was obtained from the shelter, and it was found that the animals were examined for VL according to the Ministry of Health guidelines (TR DPP® fast test oand ELISA tests) and treated according to clinical signs. In our study, 98 dogs were evaluated and physical-clinical examinations, blood collection and medullary aspirate were performed. Venous puncture was performed in the cephalic, femoral or jugular veins and 3 and 5mL were collected from each animal. L. infantum infection was confirmed by ELISA and anti-Leishmania antibody levels determined with soluble Leishmania antigens (SLA). The cutt-off was 0.392, the is value was determined based on the average of the serum results of 6 healthy animals from an area not endemic for canine VL. The bone marrow aspirate was homogenized and incubated in modified minimum essential medium (HOMEM) containing 10% of heat inactivated fetal calf serum and hemin (8 µM). The search for the parasite in each culture/aspirate was performed on alternate days by optical microscopy up to 30 days after collection. Positive isolates for Leishmania by quantitative PCR (Quiagen extraction kit) were typed with specific primers for L. infantum. The q-PCR was also used for Ehrlichia canis and Babesia sp. (SYBR green reagent -Invitrogen, Grand Island, NY, USA). DNA concentration from each sample was estimated by spectrophotometry at 260 nm. An estimate of parasite load in bone marrow aspirates was obtained through amplification of kinetoplast L. infantum DNA (kDNA) and MAG-1 using a specific set of primers and probes as previously described. DNA of E. canis and Babesia sp. were detected through a pair of primers and SYBR green reagent (Invitrogen, Grand Island, NY, USA). Thermal cycler was an initial denaturation step at 95° C for 10 minutes, followed by 40 amplification cycles (95° C for 15 seconds and 60 ° C for 60 seconds) at Quantstudio 3 qPCR Machine (Thermo-Fisher, Waltham, Massachussets, USA). CDC light traps were installed at four different points, two points in the shelter and two on private property located in a remnant area of Atlantic Forest in Nísia Floresta. Traps were set at 6 pm and removed at 6 am. Two traps were installed inside a chicken coop located in the middle of an orchard in shelter property and two traps were installed inside building where the dogs were housed. Sand flies were captured between April and December 2022. For testing the null hypothesis of no association between two categorical variables, Pearson and Fisher chi-square tests were used. To infer which predictors would be associated with a specified response variable, commonly associated with the risk of VL, a generalized linear models (GLM) were used. Presence of anti-Leishmania antibodies was estimated by the optical density (OD) of the ELISA reaction using a SLA and OD results were used in the statistical analysis. Of the 98 dogs, 70% came from the municipality of Parnamirim, followed by Natal, São Gonçalo do Amarante, Nísia Floresta and Macaíba. The most frequent clinical signs suggestive of canVL were skin lesions, onychogryphosis and conjunctivitis. Dogs older than 7 years were more likely to be positive for Leishmania than the ones younger than 1 year. Of the DNA samples 19% were positive for L. infantum. The qPCR for E. canis and B. canis infections showed that 22% dogs were positive for E. canis and 18% were positive for the protozoan Babesia sp. According to the GLM model, there was no influence of Ehrlichia and Babesia infection results on L. infantum ELISA test or qPCR. The relationship between pathogens and deaths were significant for L. infantum MAG (P < 0.01) and Ehrlichia (P = 0.04). For dogs with positive for MAG1 the odds of dying were increased by a factor of 4.55; whereas if they were positive for Ehrlichia canis the odds of dying increased by a factor of 2.75. No association was found for death and Babesia infection. L. longipalpis was the most frequent species of sand fly captured in the shelter, being more abundant in the dog shelter (96%) followed by a chicken coop on the private property. Quantitative PCR (qPCR) is the gold standard test for quantifying the parasite load. It can be used to diagnose and monitor infection during treatment. This study also showed that presence of Leishmania DNA correlated with level of anti-leishmania antibodies. Finally, the lack of population control and abandonment of dogs can cause health, social and environmental disorders in underdeveloped countries or regions. The ecossistems instability, high density of animals and infectious diseases in shelters in endemic areas can increase the spread of diseases, favoring the transmission of L. infantum. The population management of dogs in urban areas requires educational measures and requires the implementation of public, sanitary and ecological policies that are environmentally sustainable, inserting themselves in the concept of one health and benefiting both animals and people.